OSH MANAGEMENT SYSTEM IMPLEMENTATION IN PT NOJORONO TOBACCO INTERNATIONAL - Ardi Surya Satria Ridwan; Fransisscus Allessio (Universitas Darussalam Gontor, 2017)
PT Nojorono Tobacco International is one of the biggest cigarette factories in Indonesia. This company has a commitment to implement Occupational Health and Safety Management System (SMK3) based on PP No 50 Tahun 2012 with a purpose to reduce the number of workplace accidents. The purpose of this reserach is to know about the goal and steps that has been taken to implement SMK3 plans in PT Nojorono Tobacco Internationa, also an adaption that doing by company with the impementation of SMK3 and the fuctions from HRD department to support the implementation of SMK3.This research uses descriptive method and the data was collect by interview. As result, the goal from the implementation of SMK3 in PT Nojorono Tobacco International to achieve zero accident workplace with steps that has been taken is Safety plans with the adaption, determine commitment and policy of Occupational Health and Safety, training about SMK3, and form organization structure, and Occupational Health that doing by company is doing Hazard Identification and Risk Assestment that followed by Personal Protective Equipment (PPE) usage rule Hazard Identification Risk Assessment that followed by PPE usage rule.The functions from HRD Department to support the implementation of SMK3 in PT Nojorono Tobacco International is form Health, Safety, and Environment (HSE) division and give training about K3. Key words: SMK3, PT NTI, Workplace Accident